2011
DOI: 10.1177/0044118x11411933
|View full text |Cite
|
Sign up to set email alerts
|

Families, Neighborhood Socio-Demographic Factors, and Violent Behaviors among Latino, White, and Black Adolescents

Abstract: Youth violence is a major cause of morbidity and mortality among Blacks and Latinos. Violent behaviors within Latino subgroups and the reasons for subgroup differences are not well understood. Using data from the National Longitudinal Study of Adolescent Health (N = 16,615), this study examined the risk for violent behaviors among an ethnically diverse sample of youth, with special attention to different Latino subgroups. Family dynamics were examined as moderators between neighborhood socioeconomic status (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Indeed, exposure to NLEs is associated with a greater likelihood of developing externalizing behaviors such as aggression, substance abuse, and delinquency (Estrada-Martínezet al, 2013;King, Molina & Chassin, 2010). A study by Estrada-Martínez et al (2013) examined the moderating effects of family dynamics on neighborhood SES and delinquency in a sample of Black, White, and Latino youth. In particular, youth who experienced high levels of family conflict displayed more violent behavior than those with low levels of family conflict.…”
Section: Negative Life Events and Delinquencymentioning
confidence: 99%
“…Indeed, exposure to NLEs is associated with a greater likelihood of developing externalizing behaviors such as aggression, substance abuse, and delinquency (Estrada-Martínezet al, 2013;King, Molina & Chassin, 2010). A study by Estrada-Martínez et al (2013) examined the moderating effects of family dynamics on neighborhood SES and delinquency in a sample of Black, White, and Latino youth. In particular, youth who experienced high levels of family conflict displayed more violent behavior than those with low levels of family conflict.…”
Section: Negative Life Events and Delinquencymentioning
confidence: 99%
“…Finally, the current study only examined the effects of one potential moderator, marital satisfaction, while many other moderators are likely at play in explaining reductions in parenting stress and child behavior problems as a result of the MBSR intervention. Limited studies examining moderators of child intervention outcomes have found that factors such as family cohesion, parental engagement, child temperament, parent dysfunction, and child-rearing practices moderate the effects of interventions on child outcomes (Estrada-Martinez, et al, 2013;Jessee, et al, 2012;Kazdin, 1997; Downloaded by [Universite Laval] at 04:34 05 March 2015 Gerstein, et al, 2009). Future research is needed to provide a more comprehensive examination of potential moderators, as well as replicate these results.…”
Section: Downloaded By [Universite Laval] At 04:34 05 March 2015mentioning
confidence: 99%
“…Previous research has underscored the impact that family environment plays on child development and parental mental health; however, research looking at environmental influences as potential mediators and moderators of intervention outcomes is rare (Lochman, Wells, Qu, & Chen, 2013). Limited studies have found that factors such as family cohesion, parental engagement, child temperament, parent dysfunction, and child-rearing practices moderate the effects of interventions on child outcomes (Beauchaine, Webster-Stratton, & Reid, 2005;Estrada-Martinez, et al, 2013;Jessee, et al, 2012;Kazdin, 1997;Gerstein, et al, 2009). Most relevant to the current study, Beauchaine and colleagues (2005) found that marital satisfaction moderated child outcomes in the Incredible Years Parent Training Program (WebsterStratton, 1984), specifically that for mothers reporting low marital satisfaction, interventions that included a parent training (as opposed to a child or teacher component) resulted in better outcomes with regard to externalizing behavior problems at 1-year posttreatment compared to interventions without parent training.…”
mentioning
confidence: 99%
“…To further support this argument, Erickson's (1959Erickson's ( , 1968) psychosocial theory of development may have relevance when understanding and contextualizing the development of Black youth because the focus is on intrapsychic conflict related to developmental stages that determine personal identity and positive development. Applying this model to early and middle adolescence, the first developmental challenge is related to a sense of identity, the acquisition and understanding of "self," and the ability to share this "self" with others in a positive manner (Erikson, 1968). When adolescents lack this understanding, intrapsychic conflict occurs and youth are unable to successfully navigate such a crisis.…”
Section: Department Of Health and Human Service 2016)mentioning
confidence: 99%
“…Beyond teaching and running a private practice of psychology, professionals in various psychological disciplines often search for alternate means to employ their professional skills and proficiencies in service to communities all across the nation. Such expertise is needed the most in Black and other communities of color, where a disproportionate number of youth struggle to successfully navigate their way through the developmental and social challenges of childhood and adolescence (Ashiabi & O'Neal, 2015;Blum et al, 2000;Estrada-Martinez et al, 2011). Youth struggle with challenges at home, at school, and in the streets of their community, hoping to find satisfaction and success in the midst of circumstances that make poverty, single parent households, low academic achievement, teen pregnancy, drug use and abuse, crime, and violence, differential policing, and lack of viable employment opportunities all too common occurrences (Caldwell, 2011).…”
mentioning
confidence: 99%